EFFECTS OF CLIMATE CHANGE ON GULLY EROSION ADAPTATION STRATEGIES IN ORUMBA NORTH LGA, ANAMBRA STATE (FEDPOD Journal of Multidisciplinary Innovations and Perspectives, 2026)
This study aims to investigate effects of climate change on gully erosion adaptation strategies in Orumba North Local government area of Anambra State. To achieve this aim, three objectives were formulated to guide the study. Relevant literature was reviewed based on the topic. The study adopted a descriptive design with a population size of 11,250. The random sampling technique was adopted to select a sample size of hundred (100) from the study area. A structured questionnaire was used to obtain data from the respondents. The completed copies of the instrument were collated and analyzed using mean and standard deviation. The results amongst others show that climate change led to heavy rainfall, high temperature, changes in seasonal rainfall, increase flash storms and soil degradation all increased the severity of gully erosion, poor agricultural practices, heavy rains, urbanization and certain soil all contribute to the causes of gully erosion and reforestation initiatives, soil conservation techniques, community awareness programs, construction of check dams and collaborative projects with NGOS and stakeholders to develop and implement erosion management plans are possible strategies used by the local government to mitigate and manage gully erosion in Orumba North local government area of Anambra State. It was there recommended that the policy makers should develop policies that address the impacts of climate change on gully erosion, focusing on infrastructure improvements to manage heavy rainfall and runoff, encourage sustainable farming practices to reduce soil degradation and mitigate erosion causes and strengthen partnerships with NGOs to implement reforestation and erosion management initiatives effectively.